2018
DOI: 10.1007/s10620-018-5265-3
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobin A1c Has Suboptimal Performance to Diagnose and Monitor Diabetes Mellitus in Patients with Cirrhosis

Abstract: HbA1c inaccurately represents chronic glycemia in patients with cirrhosis, likely in relation to increased glucose variability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…Given the strong interrelationship between the metabolic syndrome and NASH, the FILI score needs to be further validated following interventions not targeting weight loss and an improved metabolic profile. Also, since hemoglobin A1c loses accuracy in the setting of cirrhosis-especially if decompensated-it is less clear whether this index can be reproduced patients with F4 staging (63).…”
Section: Dynamic Changes In Niald Following Therapeutic Strategiesmentioning
confidence: 99%
“…Given the strong interrelationship between the metabolic syndrome and NASH, the FILI score needs to be further validated following interventions not targeting weight loss and an improved metabolic profile. Also, since hemoglobin A1c loses accuracy in the setting of cirrhosis-especially if decompensated-it is less clear whether this index can be reproduced patients with F4 staging (63).…”
Section: Dynamic Changes In Niald Following Therapeutic Strategiesmentioning
confidence: 99%
“…A1c value can also be affected unpredictably by blood transfusion[ 100 , 101 ]. More importantly, the inherent biochemical characteristics of the glycation process limit the ability of A1c to capture the excessive blood glucose lability exhibited by patients with CLD, as demonstrated in a recent study that compared A1c against continuous glucose monitoring in diabetic patients with cirrhosis[ 102 ]. This shortcoming may have crucial clinical implications since glycemic variability was shown to be an independent predictor for fibrosis in NAFLD as well as cardiovascular disease and all-cause mortality in the general population[ 103 , 104 ].…”
Section: Traditional Glycemic Markers For Patients With Liver Diseasementioning
confidence: 99%
“…Indeed, an older study on a small cohort of cirrhotic patients demonstrated an inverse correlation between fructosamine levels and serum albumin levels [ 113 ]. A more recent study comparing fructosamine against continual glucose monitoring confirmed the poor association in diabetic patients with cirrhosis[ 102 ]. Several entities, including albumin-corrected fructosamine, total protein-corrected fructosamine, and CLD-A1c, have been proposed in an attempt to improve the diagnostic performance of GA and fructosamine by correcting for variations in serum protein concentrations[ 114 , 115 ].…”
Section: Non-traditional Glycemic Markers For Patients With Liver Dismentioning
confidence: 99%
“…69 Glycated hemoglobin A1c (HBA1c) is a reliable test to assess chronic glycemia in patients with T2DM, but has suboptimal performance in patients with cirrhosis. 70 A normal HbA1c may not necessarily rule out T2DM in the setting of cirrhosis and in patients with decompensated cirrhosis. 70 Fructosamine may be a better marker to assess glycemic control in patients with cirrhosis and T2DM, 71 but validated laboratories cut-offs do not exist at present.…”
Section: Type 2 Diabetesmentioning
confidence: 99%
“…70 A normal HbA1c may not necessarily rule out T2DM in the setting of cirrhosis and in patients with decompensated cirrhosis. 70 Fructosamine may be a better marker to assess glycemic control in patients with cirrhosis and T2DM, 71 but validated laboratories cut-offs do not exist at present. With the exception of metformin, most of the established, older antiglycemic medications are weight-promoting (i.e., glicazides, thiazolidinediones, insulin), which may in turn worsen adiposity and potentially portal hypertension in NASH cirrhosis.…”
Section: Type 2 Diabetesmentioning
confidence: 99%